Paleoclimate Variations Spanning the Past 29–4 Ma Inferred From Lipid Biomarkers and Carbon Isotopes in the Linxia Basin, Northeast Tibetan Plateau - Wang, Gen; Wei, Zhifu; Zhang, Ting; He, Wei; Ma, Xueyun; Yu, Xiaoli; Wang, Yongli (Frontiers in Earth Science, 2022)
Thick and continuous deposits in the Linxia Basin, located in the landing area of westerlies and monsoons, offer a good opportunity for understanding the climatic evolution and tectonic activities. However, detailed paleoclimate reconstruction based on lipid biomarkers was rare, which limited our further knowledge, even though there were some relevant reports regarding pollen assemblages, microbial communities. In the present study, we conducted systematic analyses on the lipid biomarkers and carbon isotope values of the sediments, in an effort to reconstruct the evolution history of paleoclimate and figure out the potential driving mechanism. Our results showed that the organic matter was from mixed sources including lower organisms and terrestrial higher plants. The organic matter sources varied in response to the change of paleoclimate conditions as revealed by the lipid-derived proxies and organic carbon isotopes. Significant climatic events like late Oligocene Warming, Mid-Miocene Climatic Optimum and aridification at ~8.5 Ma were observed throughout the sequence. Our results further indicated that the paleoclimate conditions in the study area primarily followed the pace of long-term global cooling, and the aridification at ~8.5 Ma was associated with the uplift of the Tibetan Plateau.